2019
DOI: 10.1177/2150132719847383
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure Prophylaxis (PrEP) Awareness Is Low Among Heterosexual People of Color Who Might Benefit From PrEP in Philadelphia

Abstract: Introduction: We assessed awareness of pre-exposure prophylaxis (PrEP) among HIV-negative Black and Latinx persons living in the Philadelphia Metropolitan Statistical Area. Methods: Using chi-square and Wilcoxon rank-sum tests, we analyzed data from the 2016 heterosexual cycle of the National HIV Behavioral Surveillance system to assess how sociodemographic factors, health care utilization, and risk behaviors affected PrEP awareness. Results: Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This finding has implications for PrEP engagement and access among African American men, especially MSM. Public health messages that destigmatize and normalize the potential benefits of PrEP for all individuals, irrespective of sexual and gender identity, who use condoms inconsistently and have concurrent sexual partners and/or those with unknown HIV status [ 53 ] may help improve attitudes toward PrEP among cisgender heterosexual and LGBTQ + African American young men engaging in high-risk behaviors. Other studies have documented that African American men are uncomfortable discussing or disclosing their sexual behaviors with their providers [ 9 , 54 ], stemming from medical mistrust and perceived risk of discrimination [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding has implications for PrEP engagement and access among African American men, especially MSM. Public health messages that destigmatize and normalize the potential benefits of PrEP for all individuals, irrespective of sexual and gender identity, who use condoms inconsistently and have concurrent sexual partners and/or those with unknown HIV status [ 53 ] may help improve attitudes toward PrEP among cisgender heterosexual and LGBTQ + African American young men engaging in high-risk behaviors. Other studies have documented that African American men are uncomfortable discussing or disclosing their sexual behaviors with their providers [ 9 , 54 ], stemming from medical mistrust and perceived risk of discrimination [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the patient perspective, a survey conducted among heterosexual adults in Philadelphia found that PrEP awareness was low (4.9%), and high-risk behavior was not associated with higher PrEP awareness. 20 From the provider perspective, a survey of 363 HIV providers assessing attitudes about PrEP found that providers were least likely to consider prescribing PrEP to heterosexuals. 21 A major challenge in identifying patients at the highest risk for HIV transmission is reliance on knowing the risk status of one's partners.…”
Section: Discussionmentioning
confidence: 99%
“…Lower fractions of PrEP prescriptions among those with undetermined risk are likely multifactorial including decreased awareness and other patient-level and provider-level factors. From the patient perspective, a survey conducted among heterosexual adults in Philadelphia found that PrEP awareness was low (4.9%), and high-risk behavior was not associated with higher PrEP awareness 20 . From the provider perspective, a survey of 363 HIV providers assessing attitudes about PrEP found that providers were least likely to consider prescribing PrEP to heterosexuals 21 …”
Section: Discussionmentioning
confidence: 99%